eLite exercise - M Said, Salasiah; Tarsik, Nor Famiza; Abdullah, Nurulannisa; Md Yatim, Norhidayu; Fadzil, Faizal Haini (Universiti Teknologi MARA, Kedah, 2018)
Understanding and managing library literacy class can be hard. It requires a lot of understanding in knowing the library classification scheme, knowing how to find out the materials needed and so on. eLite Class is a best tool for novice users in a library, in understanding and comprehending their lesson learnt from the Library Literacy Classes. It is an interactive exercise of answering question about what they had learnt during Library Literacy Class which simple and easy to use. Specifically the development of this eLite Class is for new students who are entering to the university (Semester 1), which are recommended for new students in UiTM, for example. eLite Exercise wil be assess from variety sections learnt in a Library Literacy modules, such as learning how to use online databases, how to use Boolean search, WildCat search, learning how to read call number and so on. eLite Exercise is work great on personal computers, mobile computers, for whole group or small group instruction or use in the computer lab or at home as individual learning. Novelty and Uniqueness: eLite Exercise adopted multimedia technologies and applications to create exciting literacy exercise innovation in the age of information evolution. This product is developed for new students who are novice users in searching the information in academic field. Students will be examined by answering the questions based on the modules taught by the library instructor. eLite Exercise also can be used for researchers, librarians as well as professionals. It is an information literacy platform that provides questions related to library instructions that is easy to use and educational. eLite Exercise is interactive, fun and comprehensive, which helps educators, especially librarians, teach, and students learn how to become effective and organized researchers